Development of differential protection scheme using positive sequence current for a microgrid - Hassan, Zaid Tariq (2022)
The microgrid (MG) is a developed form of the distribution network integrated with different distributed generation (DG) types to supply local demand. MG protection is a challenge typically due to the growing penetration of DG. Therefore, traditional protection schemes are not appropriate for the MG system. Therefore, an appropriate protection scheme should be designed to protect the MG against all types of faults for both grid-connected and islanded modes for loop and radial configuration. This research presents a comprehensive protection scheme for an inverter-based MG. This scheme proposed an index based on positive sequence current to differentiate between fault on the protected line and fault at other lines. This index was applied as a means of the differential protection scheme for MG with multi-sources. Also, the scheme proposed a new R-ratio method to provide self-backup protection when the main protection fails. This method could overcome the low fault current problem of DG in the islanded mode. In order to evaluate the confirmation of the proposed scheme, a complete fault analysis for all selected locations in the MG test system has been carried out by using PSCAD/EMTDC software. The case studies considered in this study include single line-to-ground fault (SLGF), line-to-line fault (LLF), double-line-to ground fault (DLGF), and three-line to ground fault (LLLGF) for both operation modes, grid-connected and islanded, for radial and loop configuration. Also, an unbalanced load was tested. The results show that the maximum fault clearing time for the main protection in grid-connected mode and islanded mode of 31.5 ms and 34 ms respectively. In contrast, the maximum fault clearing time for backup protection in grid-connected and islanded modes is 115.5 ms and 130 ms, respectively. Compared with other schemes, adaptive, signal processing, overcurrent, fault current limiter and traditional differential in terms of the operation speed of protection scheme and the existing backup protection, the proposed scheme has a faster clearing time.